Implementation and Usefulness of Telemedicine During the COVID-19 Pandemic: A Scoping Review. (December 2020) - Hincapié, María Alejandra; Gallego, Juan Carlos; Gempeler, Andrés; Piñeros, Jorge Arturo; Nasner, Daniela; Escobar, María Fernanda
Objectives: Identify and summarize the available literature on the acceleration in the use of telemedicine in the midst of the COVID-19 pandemic, with an aim to provide justification and guidance for its implementation to overcome the limitations associated with the pandemic worldwide. Methods: We conducted a scoping review through different search strategies in MEDLINE and Google Scholar to identify the available literature reporting data on implementation and usefulness of various modalities of telemedicine during the current pandemic. We summarized the included studies according to field and mode of implementation in a narrative way. Results: We included 45 studies that fulfilled selection criteria. About 38% of the studies were conducted in the United States of America (USA), followed by 15.5% in India and 15.5% in China. Most studies (73%) were cross-sectional studies based on historical records. All publications were written in English with the exception of 1 studied published in Spanish. The majority of reports focused on use of telemedicine for outpatient care, followed by in-hospital care. Conclusion: The COVID-19 pandemic has promoted the use of telemedicine, a tool that has transformed the provision of medical services. Several modes of implementation are useful to overcome difficulties for patient care during the pandemic. Its benefits are specific to different fields of medical practice. Such benefits, along with the guidance and reported experiences should invite health systems to work for an effective and comprehensive implementation of telemedicine in various fields.